(untitled) (CONTINUIDAD Y DISCONTINUIDAD EN EL ESPACIO IBEROAMERICANO, 2026)
El camino de Ida (2013), Ricardo Piglia’s final novel, reflects on the continuity of an anarchist literary tradition and its evolution into environmentalism; the turning point chosen to problematize it is the moment when neo-Luddite terrorism erupts as a discontinuity. Within a mostly idyllic and anti-capitalist vision, this disruption enters—both in the text and in real history—by way of the controversial biography of Theodore Kaczynski (the Unabomber, referred to as “Recycler” in the text), the brilliant mathematician who graduated from Harvard and later taught at Berkeley (who passed away in prison in 2023) and who, for nearly 20 years until 1995, kept the FBI on edge with lethal homemade bombs sent through the mail from his then-untraceable hideout.